Revisiting the Small-Firm Effect on Entrepreneurship: Evidence from Firm Dissolutions - Kacperczyk, Aleksandra; Marx, Matt (Organization Science, 2016)
Afrequent claim in the entrepreneurship literature is that employees learn to become entrepreneurs during paid employment. We revisit this mechanism in the context of the well-established finding that smaller firms generate higher rates of entrepreneurship. We propose a novel mechanism responsible for higher rates of entrepreneurship emanating from smaller firms: large firms might have a advantage over small firms in providing internal opportunities to retain entrepreneurial talent. We test this claim in a setting where firm dissolution extinguishes internal opportunities, using a new hand-collected data set of career histories in the automatic speech recognition (ASR) industry. For nondefunct firms, we replicate the “small-firm effect.” However, the small-firm effect no longer holds within the subsample of defunct firms: entrepreneurship rates among individuals present at firm dissolution are in fact higher for larger firms. Additional analyses indicate that this effect is unlikely to be driven by the early departure of higher-skilled workers who anticipate the firm’s demise. Finally, we find preliminary evidence consistent with the notion that large organizations may not only retain but also “mold” workers into entrepreneurs. More broadly, the study emphasizes the need to consider a novel mechanism responsible for transition into entrepreneurship—the role of opportunities available to employees in incumbent firms.